Söngbók séra Ólafs Jónssonar á Söndum - Ólafur Jónsson 1560-1627 (Stofnun Árna Magnússonar í íslenskum fræðum, 2024)
"The Icelandic pastor and poet Ólafur Jóhnsson (ca. 1560-1627) was one of Iceland's most beloved poets of the early seventeenth century. His poems were mostly transmitted in the substantial manuscript collections known as his Kvæðabók (Book of Poems), 26 copies of which have survived. These usually contain around 140 poems, and while most of them were sung to melodies referred to only by rubrics ("To the tune of [...]"), many of the manuscripts contain music notation. ...The present volume is not a complete edition of the Kvæðabók but contains only the 51 poems transmitted with music in seventeenth- and eighteenth-century manuscripts." -- English abstract, pages 321-322
Keywords: Ólafur Jónsson -- 1560-1627; Hymne; Christliche Lyrik; Lyrics -- Lyrik; Ólafur Jónsson / 1560-1627; Ólafur Jónsson / 1560-1627 / Musical settings; Icelandic poetry / 16th century / Musical settings; Icelandic poetry / 17th century / Musical settings; Sacred songs, Unaccompanied / Scores; Religious poetry, Icelandic; Icelandic poetry; Hymns, Icelandic; Musical settings; Religious poetry; Songs; Hymns